Effect of cationic substitutions on the photoluminescence properties of Eu2+ doped SrCN2 prepared by a facile C3N4 based synthetic approach. Issue 16 (December 2020) - Leysour de Rohello, Erwan; Suffren, Yan; Merdrignac-Conanec, Odile; Guillou, Olivier; Cheviré, François
Abstract: An alternative general approach to synthesize carbodiimide materials using carbon nitride as precursor is proposed. This new facile synthetic route was illustrated by the preparation of single phases α-SrCN2 and β-SrCN2 in a reproducible and effective manner via the substitution of barium and calcium for strontium. Structural characterizations and optical properties of Eu 2+ doped SrCN2 polymorphs were investigated on the bases of high-resolution X-ray powder diffraction and photoluminescence analyses to evaluate the potential of such systems as red phosphors. All Eu 2+ doped samples exhibit intense red emission in the 620−630 nm range when excited at 440 nm at 77 K with little impact of the crystal lattice on the emission wavelength. However, calcium and barium substitutions for strontium strongly impact the emission intensity and the emission width respectively and all doped samples have their emission intensity reduced by 50 % around 80−90 K and totally quenched at RT.